P148Cardiac myocytes are protected by small leucine rich proteoglycans against simulated ischemia/reperfusion injury. (15th July 2014) - Gaspar, R; Gorbe, A; Paloczi, J; Varga, ZV; Gomori, K; Ferdinandy, P; Csont, T
Abstract: It was previously shown by our group that the overexpression of biglycan in a transgenic mouse model enhances the induction of cardioprotective genes. Ischemia induced cell death was decreased by bigylcan treatment in neonatal cardiomyocytes. In this study we aimed to test whether the biglycan core protein or the glycosaminoglycan is responsible for the cardioprotective effect of biglycan. We also investigated whether decorin, (which has a similar structure to biglycan), has any cardio-protective effects on cardiomyocytes during simulated ischemia/reperfusion (SI/R) injury. Primary cardiomyocyte cultures were isolated from neonatal rat hearts. The 2 day-old cultures were pretreated with 0, 1, 3, 10, 30, and 100 nM decorin, biglycan, biglycan core protein or chondroitin sulfate A for 20 hours followed by an SI/R protocol. The treatment was maintained throughout SI, 240 min, hypoxic solution, hypoxic chamber gassed with 95% N2 ès 5% CO2) and reperfusion (120 min, normoxic conditions, medium). At the end of the protocol, a viability assay was performed using calcein staining. Compared to the normoxic untreated control, approximately 40% of the cardiomyocytes died during the simulated ischemia/reperfusion injury. Doses of 10 and 30 nM biglycan increased cell viability significantly, compared to SI/R control (29±4 and 18±5%). The biglycan core protein showed similar cytoprotective effects at 3 and 10 nM doses (21±4 and 24±5%), however, the chondroitin sulfate had no influence on the viability of cardiomyocytes. In the case of decorin, the 3 and 10 nM doses significantly increased the survival of the cells (28±3 and 20±4%). Based on our experiments, we concluded that both decorin and biglycan exert a cyto-protective effect on cardiomyocytes against SI/R injury and this protective effect of biglycan is likely due to the biglycan core protein. Grants: NKTM-OTKA-PD-106001, South-East European Foundation Lykeon Scholarship, GA holds Bolyai Janos Fellowship